Agents of Reform, Agents of Revolution (KULT_online, 2015)
What is the difference between reform and revolution? How are cultural values disseminated through a society, and who controls this process? What is the best form of action to effect cultural change? These are some of the questions which Reform Acts asks of the Victorian novel, specifically a group of novels written between the passage of the First (1832) and Second (1867) Reform Acts in England and Wales. Vanden Bossche explores how these narratives engaged with the Chartist movement and how they sought to grant social agency to the working classes.